The Relationship between Training Implementation and Entrepreneurial Behavior Graduates Of Makeup Training At LPK Rane Padang City - Novita Illahi, Febri; Aini, Wirdatul (Universitas Negeri Padang, 2024)
The background of this research is the low entrepreneurial behavior of cosmetology training graduates at the Keja Rane Training Institute, which is suspected because the implementation of the training at the Keja Rane Training Institute in Padang City is not good. This study aims to reveal the description of the implementation of the training in the tying training at LPK Rane, the entrepreneurial behavior of graduates of the cosmetology training at LPK Rane, and reveal the relationship between the implementation of the training and the entrepreneurial behavior of training graduates at LPK Rane, Padang City. This study uses a quantitative approach with a correlational type. The population in this study were 32 cosmetology training graduates, while the sample was taken using a simple random sampling technique of 78%, namely 25 people. Data collection techniques using a questionnaire. And the technique used in data analysis is the percentage formula and the spearman rho formula correlation. The results of this study indicate that: 1) the implementation of training in cosmetology training at LPK Rane is still relatively low, 2) entrepreneurial behavior of training graduates is low, 3) there is a significant relationship between training implementation and entrepreneurial behavior of cosmetology training graduates at LPK Rane Padang city.Keywords: Implementation Of Training, Entrepreneurial Behavior